Rising tides of knee osteoarthritis: global trends and regional disparities among middle-aged and elderly populations from 1990 to 2021 and its prediction to 2035 - Chen, Yufan; Wang, Zhiwei; Xu, Zhaoyi; Chen, Liyi (Frontiers in Musculoskeletal Disorders, 2025)
ObjectiveThis study aims to analyze the global disease burden of knee osteoarthritis (KOA) among middle-aged and elderly populations (aged ≥45 years) from 1990 to 2021, project trends to 2035, and evaluate disparities across sociodemographic index (SDI) regions, age groups, and genders.MethodsData from GBD 2021 assessed KOA prevalence, incidence, years lived with disability (YLDs), and age-standardized rates (ASRs) across 204 countries (1990–2021). Age-period-cohort (APC) modeling to disentangle age/time/cohort effects. Joinpoint regression to quantify temporal trends (annual percent change, APC; average APC, AAPC). Bayesian forecasting for 2035 projections. Socioeconomic disparities assessed via slope index (SII) and concentration index (CI).ResultsFrom 1990 to 2021, global KOA incidence and prevalence increased by 1.3-fold [age-standardized incidence rate (ASIR): +7.3%, from 978.74 to 1,050.31/100,000] and 1.4-fold [age-standardized prevalence rate (ASPR): +8.4%, from 13,596.63 to 14,741.08/100,000], respectively. Females exhibited higher burdens than males [ASPR: +8.4%; age-standardized years lived with disability rate (ASYR): +8.3%]. High SDI regions reported the highest ASIR (1,162.95/100,000) and ASPR (16,029.60/100,000), whereas low SDI regions had the lowest rates (ASPR: 12,150.70/100,000). By 2035, global prevalence is projected to reach 482 million, with ASPR rising to 15,058.08/100,000. It is estimated that there will be 34,372,090 incidence cases globally, and YLDs are expected to reach 15,386,065 years by 2035.ConclusionThe prevalence, incidence, YLDs, and ASRs of KOA have increased substantially in most countries and regions from 1990 to 2021. The burden of KOA appears to rise with increasing SDI and is higher in females than in males. Population aging has exacerbated the burden of KOA, whereas transnational inequalities have not improved significantly. Gender-specific interventions, SDI-tailored policies, and strengthened healthcare systems are essential to address this increasing public health challenge.